2013
DOI: 10.1155/2013/759274
|View full text |Cite
|
Sign up to set email alerts
|

Kantowski-Sachs String Cosmological Model with Bulk Viscosity in General Scalar Tensor Theory of Gravitation

Abstract: A new class of spatially homogeneous Kantowski-Sachs string cosmological models with bulk viscosity in Nordtvedt (1970) general scalar-tensor theory of gravitation with the help of a special case proposed by Schwinger (1970) is obtained. In this paper we have presented anisotropic as well as isotropic cosmological models. Some important features of the models, thus obtained, have been discussed. These exact models are new and more general and represent not only the early stages of evolution but also the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The density perturbation arising out of them plays an important role in cosmology since they are considered as the route for galaxy formation. After Stachel [21] and Hendi and Momeni [22] many researchers [23][24][25][26][27][28][29][30][31][32] have worked on string cosmological models in the context of Einstein's theory or modified theories of gravity. Pradhan et al [33] studied the LRS Bianchi type-II massive string cosmological model in general relativity.…”
Section: Introductionmentioning
confidence: 99%
“…The density perturbation arising out of them plays an important role in cosmology since they are considered as the route for galaxy formation. After Stachel [21] and Hendi and Momeni [22] many researchers [23][24][25][26][27][28][29][30][31][32] have worked on string cosmological models in the context of Einstein's theory or modified theories of gravity. Pradhan et al [33] studied the LRS Bianchi type-II massive string cosmological model in general relativity.…”
Section: Introductionmentioning
confidence: 99%
“…Sahu, Nayak and Behera [26] have found that Bianchi type-I cosmological models do not exist in bimetric theory of gravitation in presence of viscous fluid or mesonic viscous fluid with or without a mass parameter in general. Further, Kantowski-Sachs cosmological models are also studied by different authors like Tiwari and Dwibedi [27], Rahaman, Chakraborty, Bera and Das [28], Chaubey [29], Rao and Neelima [30], Adhav, Dawande and Raut [31], Hector Martinez and Carlos Peralta [32] in different angles.…”
Section: Introductionmentioning
confidence: 99%